BCG as Diagnostic Test for Primary Tuberculosis in Children - Widiatmodjo Widiatmodjo; Yati Soenarto; Budi Susatyo; Sunartini Iman; Sulistyowati Sulistyowati; Ismangoen Ismangoen (Paediatrica Indonesiana, 1983)
BCG and PPD Mantoux Intradermal Test were done simultaneously on 35 children suffering from primary tuberculosis hospitalized in the Department of Child Health, School of Medicine, Gajah Mada University, Yogyakarta, Indonesia, during the period of June 1980 to November 1980. This study revealed that: The BCG test was almost three times (74.3%) more sensitive than the PPD Mantoux Intradermal test in children suffering from primary tuberculosis. In under-nourished children with tuberculosis, the BCG test was even more sensitive (85.0% : 25.0%) and this difference was statistically significant (P < 0.01). There was a high frequency of false negative tuberculine reaction (74.3%) and accelerated BCG reaction (74.3%) in primary tuberculosis. It is suggested that BCG test be used as a diagnostic test as well as prophylactic in tuberculosis children who have had a BCG vaccination.